2022
DOI: 10.29303/jppipa.v8i1.1100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Use of the Approach of Blended Learning Model Rotation Based Moodle on Motivation and Cognitive Abilities of Students in the Subjects of Physics

Abstract: Students' motivation to learn is the main aspect to achieve student success. Based on the results of observation and interview, the learning motivation of students in SMA Negeri 2 Kutacane is still relatively less, so the impact on the low cognitive ability of the students. The purpose of this study is to see the influence of the approach blended learning type station rotation on differences in motivation and cognitive abilities after the study. This research use approach uses quasi-experiments design pretest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Several previous research results also show that the demographic variables of the respondents also affect several other latents, including gender on acceptance of learning with e-learning [14], gender also affects student learning styles [15], and the relationship between the use of e-learning on learning outcomes [16]. Besides that, related to online lectures, many studies have been carried out, including those related to the use of time during online lectures [17], implementation of STEM modules on E-Learning media [18], the effect of using Blended Learning on Motivation and Cognitive Ability [19], development of three-tier diagnostic test based on E-Learning [20], the effect of using the internet as a learning medium on learning outcomes [21], and the effect of remediation of misconceptions with E-Learning media [22].…”
Section: The Level Of Student Satisfaction From the Aspect Of The Stu...mentioning
confidence: 99%
“…Several previous research results also show that the demographic variables of the respondents also affect several other latents, including gender on acceptance of learning with e-learning [14], gender also affects student learning styles [15], and the relationship between the use of e-learning on learning outcomes [16]. Besides that, related to online lectures, many studies have been carried out, including those related to the use of time during online lectures [17], implementation of STEM modules on E-Learning media [18], the effect of using Blended Learning on Motivation and Cognitive Ability [19], development of three-tier diagnostic test based on E-Learning [20], the effect of using the internet as a learning medium on learning outcomes [21], and the effect of remediation of misconceptions with E-Learning media [22].…”
Section: The Level Of Student Satisfaction From the Aspect Of The Stu...mentioning
confidence: 99%
“…According to Osborne et al (2003), the ability of teachers to be able to contextualize science material following the daily experiences of students, clarity in communicating the learning objectives to be achieved, and the ability of teachers to be able to facilitate various types of cognitive styles of students are factors that influence student success in learning science. Dari et al (2022) research shows that students' low motivation in studying physics has an impact on the low cognitive abilities of students. Furthermore, Dari et al (2022) state that teachers' use of conventional learning strategies leads students to memorize various facts rather than understand concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Dari et al (2022) research shows that students' low motivation in studying physics has an impact on the low cognitive abilities of students. Furthermore, Dari et al (2022) state that teachers' use of conventional learning strategies leads students to memorize various facts rather than understand concepts. Another study was conducted by Rezeki et al (2021), which showed that low concept understanding was one of the obstacles for students in learning science.…”
Section: Introductionmentioning
confidence: 99%
“…In the blended learning method, the process of digesting information occurs formally and informally. In addition to the learning process being guided by teachers in face-to-face and online, students' knowledge can also be accompanied by utilizing technology and media available through the internet (Dari et al, 2022). In blended learning, using a learning management system is not enough without good planning.…”
Section: Introductionmentioning
confidence: 99%